2011
DOI: 10.2298/bah1102197g
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the prebiotic Salgard and a herb mixture on Pekin ducklings in organic poultry production, part II: Histological and microbiological investigation

Abstract: The purpose of this investigation was to study the influence of the prebiotic Salgard and an herb mixture (rosemary, thyme, basil, oregano and cinnamon) on the histostructure of some internal organs and on the intestinal microflora of Pekin ducklings in an organic production system. Seventy two Pekin ducklings distributed randomly into 3 groups of 24 birds each and sexed (12 ♂and 12 ♀) were used as followed: group I (control) fed a standard diet; group II-fed the same diet supplemented with the prebiotic Salga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…They suggest that medicinal plants decrease the total harmful bacteria in the intestinal wall and cause a reduction in production of toxic compounds and damage to intestinal epithelia cells such as shorter villi and deeper crypt. That explanation supported by those obtained by (Gerzilov et al, 2011b) they showed that using of herb extract for Pekin duckling non significantly increased intestinal villi when compared with the control. Regarding MWT, it was observed that magnetic water increase intestinal villi length which confirm improvement of nutrient absorption and body weight of growing Pekin ducklings when compared with control.…”
Section: Intestinal Histopathologysupporting
confidence: 71%
“…They suggest that medicinal plants decrease the total harmful bacteria in the intestinal wall and cause a reduction in production of toxic compounds and damage to intestinal epithelia cells such as shorter villi and deeper crypt. That explanation supported by those obtained by (Gerzilov et al, 2011b) they showed that using of herb extract for Pekin duckling non significantly increased intestinal villi when compared with the control. Regarding MWT, it was observed that magnetic water increase intestinal villi length which confirm improvement of nutrient absorption and body weight of growing Pekin ducklings when compared with control.…”
Section: Intestinal Histopathologysupporting
confidence: 71%
“…A significant bactericidal and fungicidal activity is displayed also by Chenopodium botrys L., Chenopodiaceae (Maksimović et al, 2005) and Ambrosia artemisiifolia L., Asteraceae (Chalchat et al, 2004). The addition of prebiotic and herb mixture (resemary, thyme, sweet basil, oregano and cinnamon) to the diet of Pekin ducklings contributed to reduction of pathogenic intestinal microorganisms (Gerzilov et al, 2011).…”
Section: Antimicrobial Activity Of Plantsmentioning
confidence: 99%